A simple approach for non‐invasive transcranial optical vascular imaging (nTOVI). Issue 11 (29th April 2015) - Kalchenko, Vyacheslav; Israeli, David; Kuznetsov, Yuri; Meglinski, Igor; Harmelin, Alon
Abstract : In vivo imaging of cerebral vasculature is highly vital for clinicians and medical researchers alike. For a number of years non‐invasive optical‐based imaging of brain vascular network by using standard fluorescence probes has been considered as impossible. In the current paper controverting this paradigm, we present a robust non‐invasive optical‐based imaging approach that allows visualize major cerebral vessels at the high temporal and spatial resolution. The developed technique is simple to use, utilizes standard fluorescent dyes, inexpensive micro‐imaging and computation procedures. The ability to clearly visualize middle cerebral artery and other major vessels of brain vascular network, as well as the measurements of dynamics of blood flow are presented. The developed imaging approach has a great potential in neuroimaging and can significantly expand the capabilities of preclinical functional studies of brain and notably contribute for analysis of cerebral blood circulation in disorder models.An example of 1 × 1.5 cm color‐coded image of brain blood vessels of mouse obtained in vivo by transcranial optical vascular imaging (TOVI) approach through the intact cranium. Abstract : A simple and robust experimental technique is presented, specially developed for imaging of brain vascular network through the intact cranium in vivo . This approach is based on the application of near‐infrared fluorescent substance and dynamic color‐coding, allowing to highlight a brain vascular topography and successfully distinguish veins and arteries. The technique has a great potential in neuroimaging as it's able to be applied through the intact skin of a mouse as it shown in the article. This significantly expands the capabilities of alternative therapeutic strategies against severe brain vascular diseases like stroke.